Author Correction: Discovery and refinement of genetic loci associated with cardiometabolic risk using dense imputation maps - Iotchkova,V; Huang,J; Morris,JA; Jain,D; Barbieri,C; Walter,K; Min,JL; Chen,L; Astle,W; Cocca,M; Deelen,P; Elding,H; et al. (Nature Genetics, 2018)
Correction to: Nature Genetics https://doi.org/10.1038/ng.3668, published online 26 September 2016.In the version of the article published, the surname of author Aaron Isaacs is misspelled as Issacs.